PENGARUH CITRA MEREK DAN PERIKLANAN TERHADAP KEPUTUSAN PEMBELIAN POLIS ASURANSI - Ridho Pahlawan Tobing; Lila Bismala (Universitas Medan Area, 2015)
The aim of this research was to determine the effect of brand image and advertising on consumer purchasing decisions are made. The results showed that there is influence between the variables of brand image on purchase decisions of customers insurance policy. The second hypothesis is rejected, there is no influence of advertising on purchase decisions of insurance policies. The third hypothesis is accepted, that there is a positive influence between the brand image and the negative impact of advertising on purchase decisions of insurance policies.